Validation of succination targets and its effects on Escherichia Coli - Navarro-Porras, María José (Instituto Tecnológico de Costa Rica, 2022)
Succination is a non-enzymatic and covalent PTM of cysteine by the TCA cycle metabolite fumarate, which results in the formation of S-(2-succino)cysteine (2SC), a mitochondrial stress indicator. It causes wide-ranging effects on eukaryotic metabolism, but has not been well-established for prokaryotic organisms. Therefore, the aim of this project is to validate in E. coli some succination targets previously revealed by proteomics, of which some are proteins with Fe-S clusters. The experiments were elaborated according to two methodologies, using Dimethyl Fumarate (DMF), its active compound Monomethyl-Fumarate (MMF), and fumarase depletion ΔfumABC mutant to drive fumarate accumulation. It was demonstrated that supplementation with glutamine, adenine and xanthine (GAX) was able to overcome the toxic effect of DMF on the mutants at sub-MIC of the drug. Also, a ΔfumABC mutant manages to recover a growth rate similar to the WT strain when supplemented with GAX. For the second part, enzymatic assays were performed to measure the specific activity of fumarase and aconitase. The Fe-S proteins decreased their enzymatic activity when exposed to DMF and fumarase depletion treatments. Among all, Fe-S clusters appear to have a protecting role from succination on their coordinating cysteines. The results obtained contribute to the evidence that succination is a significant PTM and a potential key mechanism linking multiple pathways that may cause dysregulation of cell metabolism in prokaryotes.
Proyecto de Graduación (Bachillerato en Ingeniería en Biotecnológia) Instituto Tecnológico de Costa Rica, Escuela de Biología, 2022
Keywords: Fe-S clusters; TCA cycle; Fumarate; Enzymology; Enzimología; Fumarato; Escherichia coli (E. coli); Experimentos -- Dimetil; Ensayos enzimáticos; Metabolismo celular; Experiments -- Dimethyl; Enzymatic assays; Cellular metabolism; Research Subject Categories::TECHNOLOGY::Bioengineering::Enzyme engineering